First isolation of Vibrio tapetis and an atypical strain of Aeromonas salmonicida from skin ulcerations in common dab ( Limanda limanda ) in the North Sea - M Vercauteren; E De Swaef; A Declercq; L Bosseler; S Gulla; S Balboa; J L Romalde; L Devriese; H Polet; F Boyen; K Chiers; A Decostere (Journal of Fish Diseases, 2018)
Skin ulcerations rank amongst the most prevalent lesions affecting wild common dab ( Limanda limanda ) with an increase in prevalence of up to 3.5% in the Belgian part of the North Sea. A complex aetiology of these ulcerations is suspected, and many questions remain on the exact factors contributing to these lesions. To construct the aetiological spectrum of skin ulcerations in flatfish, a one‐day monitoring campaign was undertaken in the North Sea. Fifteen fish presented with one or more ulcerations on the pigmented and/or non‐pigmented side. Pathological features revealed various stages of ulcerations with loss of epidermal and dermal tissue, inflammatory infiltrates and degeneration of the myofibers bordering the ulceration, albeit in varying degrees. Upon bacteriological examination, pure cultures of Vibrio tapetis were retrieved in high numbers from five fish and of Aeromonas salmonicida in one fish. The V. tapetis isolates showed cross‐reactivity with the sera against the representative strain of serotype O2 originating form a carpet‐shell clam ( Ruditapes descussatus ). Moreover, the A. salmonicida isolates displayed a previously undescribed vapA gene sequence (A‐layer type) with possible specificity towards common dab. Further research is necessary to pinpoint the exact role of these agents in the development of skin ulcerations in common dab.

Enterococcus cecorum septicemia in a malnourished adult patient - G. Greub; L. A. Devriese; B. Pot; J. Dominguez; J. Bille (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

A comparison of methods used for testing staphylokinase (fibrinolysin) production in Staphylococcus strains - L. A. Devriese; A. Van De Kerckhove (Antonie van Leeuwenhoek, 1980)

Carbohydrate dissimilation tests in the identification of staphylococci - L. A. Devriese; A. Van De Kerckhove (Antonie van Leeuwenhoek, 1980)

Hemin-dependent mutants isolated from methicillin-resistantStaphylococcus aureus strains - L. A. Devriese (Antonie van Leeuwenhoek, 1973)